Influence of assessment site in measuring transcutaneous bilirubin - Conceição,Cristiane Maria da (2014)
Objective : To investigate the influence of the site of measurement of transcutaneous bilirubin (forehead or sternum) in reproducibility of results as compared to plasma bilirubin. Methods : A cohort study including 58 term newborns with no hemolytic disease. Transcutaneous measurements were performed on the forehead (halfway between the headline and the glabella, from the left toward the right side, making consecutive determinations, one-centimeter apart) and the sternum (five measurements, from the suprasternal notch to the xiphoid process with consecutive determinations, one-centimeter apart) using Bilicheck® (SpectRx Inc, Norcross, Georgia, USA). The correlation and agreement between both methods and plasma bilirubin were calculated. Results : There was a strong linear correlation between both determinations of serum bilirubin at the forehead and sternum (r=0.704; p<0.01 and r=0.653; p<0.01, respectively). There was correspondence of the mean values of transcutaneous bilirubin measured on the sternum (9.9±2.2mg/dL) compared to plasma levels (10.2±1.7mg/dL), but both differ from the values measured on the forehead (8.6±2.0mg/dL), p<0.05. Conclusion : In newborn term infants with no hemolytic disease, measuring of transcutaneous bilirubin on the sternum had higher accuracy as compared to serum bilirubin measurement on the forehead.